Effects of Birth Order on Performance and Affective State of Pigs - Slegers, Yara; Oolbekkink, Yoska; Roelofs, Sanne; van der Staay, F. Josef; Nordquist, Rebecca E. (Frontiers in Animal Science, 2021)
In pigs, higher birth order is associated with higher pre-weaning mortality. However, knowledge on the effect of birth order on welfare of surviving piglets is limited. The aim of this study was to explore the possible link between birth order and both newborn piglet performance and later affective state. Firstly, the following data were collected in 393 piglets from 27 litters: stillbirth, intactness of the umbilical cord and birth weight. Subsets of piglets were used to measure suckling latency (n = 67) and teat order (n = 21). Secondly, a subset of first-born (n = 9) and last-born (n = 7) piglets were trained to perform an active-choice judgement bias task (JBT). During discrimination training preceding the JBT, the pigs learned to associate two tone cues with the availability of either a large (4 M&M’s® Milk Chocolate candies) or small (1 M&M’s) reward, provided at two different locations. After training, ambiguous intermediate tones were introduced and the pig’s choice of location was scored as either optimistic or pessimistic. Results showed that last-born piglets had a higher birth weight than middle-born piglets, while first-born piglets did not significantly differ from last- or middle-born piglets. They also latched to more caudal teats than first-born piglets. The last-born and first-born piglets showed a similar learning rate during discrimination training, and a similar latency to approach reward locations, and had a similar optimistic bias in the JBT.